2021
DOI: 10.3399/bjgpo.2021.0126
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with screening for atrial fibrillation: a qualitative study in general practice

Abstract: Background/IntroductionGuidelines recommend screening for atrial fibrillation (AF). Currently screening is not considered standard care among general practitioners (GPs).AimTo explore the experiences of primary care workers with different methods of screening for AF and with implementation in daily practice.Design & settingA qualitative study using semi-structured interviews with GPs, nurses and assistants, experienced with implementation of different methods of screening.MethodTwo independent researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Previous opportunistic screening approaches in general practice have focussed on staff-led screening through pulse palpation, or hand-held devices 9,[14][15][16][17] . Only one other study, SAFE-2-SCREEN, examined patient-led screening for AF in GP waiting rooms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous opportunistic screening approaches in general practice have focussed on staff-led screening through pulse palpation, or hand-held devices 9,[14][15][16][17] . Only one other study, SAFE-2-SCREEN, examined patient-led screening for AF in GP waiting rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous opportunistic screening approaches in general practice have focused on staff-led screening through pulse palpation or hand-held devices. 9 , 14 , 15 , 16 , 17 Only 1 other study, SAFE-2-SCREEN, examined patient-led screening for AF in GP waiting rooms. The SAFE-2-SCREEN study screened a large number of patients (n = 28,340, mean age = 51.9) and achieved a detection rate of 0.68%, 18 , 19 which is in line with the known detection rate of 0.41% for people <65 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Indeed, a systematic review concluded that although screening for AF is bene cial, targeted screening is more costeffective than systematic screening. 26 Uittenbogaart et al (2022) found that clinicians like general practitioners prefer to use hand-held devices for screening of AF over methods like palpating a patient's pulse, as the reading can be saved or stored. 27 A qualitative study interviewing pharmacists using focus groups concluded that AF screening should be incorporated into general practices and prioritised for highrisk patients; 25 another qualitative research article also highlighted the importance of screening high risk patients.…”
Section: Introductionmentioning
confidence: 99%